Group portrait of the attendees of the June 1945 Methodist Youth meeting at Monte Toyon Camp - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of a Methodist Youth meeting, held June 1945 at Monte Toyon Camp in Aptos, California. In the image several goups of attendees can be seen holding signs that read: "Tracy," "Chico," "Gilroy," "Aurel," "Vallejo," "Escalon," "Soledad?," "Watsonville," "Crusaders," "Lodi," "Pacific Grove," "Patterson," "Hayward," "Theta Pi," "Huchson," "Turlock M.Y.F.," "Woodland," "Lafayette," "Colhsa," and "Vallejo Seekers."